Rhetoric and Discourse in Political Speeches - Mohammad Riza Zakariya; Nurul Chojimah; Ika Nurhayani (Universitas Brawijaya, 2018)
This research investigates the rhetoric and discourse of Susilo Bambang Yudhoyono and Joko Widodo’s speeches regarding to policies and subsidy plans about increasing the price of fuel that are capable of enhancing Indonesian economic recovery and development. Societies reacted differently after they delivered speech in different period. One factor regarding to societies’ different reaction is that the speaker had applied the variety of rhetorical devices and the involvement of discourse device toward in speeches. In accordance with this fact, the goal of this research is to find out the comparison of using persuasive strategies and the involvement of discourse devices toward their rhetorical speeches. In achieving this, the researcher employs descriptive qualitative research because it describes and interprets the process of research without any calculation. Aristotle’s theory about persuasive strategies are employed in the analysis, and then followed by Hasan and Halliday’s theory about discourse. In the findings, the researcher finds all rhetoric strategies which are applied by SBY and JOKOWI. SBY mostly logos in his speech meanwhile Jokowi uses Pathos. There is the involvement of discourse theory toward the rhetorical speeches. SBY uses conjunction, reference and lexical cohesion, meanwhile Jokowi uses ellipsis conjunction, reference and lexical cohesion.